Quantitative Evaluation of Ethnobotanicals from Dang District, South Gujarat - Kavi Oza; Ankita Thorat; Sandhya K. Garge; Vinay M. Raole (The Ethnobiological Society of Indonesia, 2022)
In the present communication we are trying to report the socio-cultural valuation of the available Phyto-resources from the Dang district, South Gujarat. Quantitative techniques have been used in ethnobotany to compare the uses and the cultural importance of different plant taxa. Researchers have developed several indices to estimate the significance of plant species for humans. We used interview and observational data concerning plants traditionally used by tribal people of south Gujarat. Individual data ‘event’ is collected and segregated in pre-defined use categories. It was then processed separately. Different indices such as User report (UR), Frequency of citation (FC), Number of uses (NU), Cultural importance index (CI), Relative frequency of citation (RFC), and Relative importance index (RI) were calculated. We found a low correlation between the practical and the cultural values of species: some species rarely used were frequently mentioned in interviews, whereas some species frequently used were rarely mentioned in interviews. Indices of cultural and practical value measure different dimensions of the importance of plant species to society. From the present study we found that Moringa oleifera is the most used plant species in the study area.